2013
DOI: 10.1017/s1365100512000405
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects of Oil Price Shocks and Their Impact on the Current Account

Abstract: Our objective is to study the dynamic effects of an oil price shock on economic key variables and on the current account of a small open economy. To do this, we introduce time non-separable preferences in a standard model of a small open economy, where labor supply is endogenous and imported oil is used both as an intermediate input in production and as a consumption good. Using a plausible calibration of the model, we show that the changes in output and employment are quite small, and that the current account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Other studies by Gruber and Kamin (2007) and Cooper (2008) found that current account deficits and imports would have been reduced by a significant amount if imported oil were relatively stable. Similarly, Schubert (2009) investigated the effects of oil price shocks on internal and external economic performance of a small open economy with particular focus on permanent increases in oil price. The findings were that after an oil price increase, the current account exhibited the J‐curve property by first deteriorating for a while and then improving.…”
Section: Oil Price Shocks and Current Account Dynamicsmentioning
confidence: 99%
“…Other studies by Gruber and Kamin (2007) and Cooper (2008) found that current account deficits and imports would have been reduced by a significant amount if imported oil were relatively stable. Similarly, Schubert (2009) investigated the effects of oil price shocks on internal and external economic performance of a small open economy with particular focus on permanent increases in oil price. The findings were that after an oil price increase, the current account exhibited the J‐curve property by first deteriorating for a while and then improving.…”
Section: Oil Price Shocks and Current Account Dynamicsmentioning
confidence: 99%
“…Against previous results, current account surplus of Chinese in Hoffmann (2013) was driven by global shocks. Schubert (2014) investigated dynamic effects of oil price shocks and their impact on the current account. Narayan (2013) employ a structural VAR model to explore the similar issue.…”
Section: Introductionmentioning
confidence: 99%
“…27 In this circumstance, in addition to the four parameters used in Figure 2 (γ = 0, ρ = 0.01, α n = 0.7, and δ = 0.025), the following parameters are added. First, in line with Schubert (2014), the initial international oil price is normalized to p = 1. Second, we consider Korea as the representative small open economy with net oil imports.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…One common feature of these studies is that their analysis is based on ad hoc behavioral specifications, and hence lacks a solid micro-foundation. The sharp rise in oil prices in the first half of 2008 led to a renewal of interest by macroeconomists in the harmful consequences arising from oil price shocks; see, e.g., Wen (2008, 2012), Blanchard and Riggi (2009), Kilian and Lewis (2011), Kormilitsina (2011), Schubert and Turnovsky (2011), Natal (2012), and Schubert (2014). Within the literature, some studies [e.g., Blanchard and Riggi (2009) and Kilian and Lewis (2011)] found that, compared with the two oil crises in the 1970s, the detrimental effect of rising oil prices in the 2000s was relatively mild.…”
Section: Introductionmentioning
confidence: 99%